Shaping Maori identities and histories : collecting and exhibiting Maori material culture at the Auckland and Canterbury museums from the 1850s to the 1920s : submitted in fulfilment of the requirement of the degree of Doctor of Philosophy, Social Anthropology Programme, School of Global Studies, Massey University, Palmerston North, New Zealand - Cameron, Fiona Ruth (Massey University, 2000)
As museums now reinterpret their collections, many or which have their foundations in the experience of colonialism, we may ponder the contextual meanings and discursive practices scripted into them during their formation. Shaping Maori identities and histories critically examines the processes of collecting and exhibiting Maori material culture at the Auckland and Canterbury Museums from the 1850s to the early 1900s. It interrogates the values, meanings and motivations that drove these processes, and the way new identities and histories were established for Maori people as a result of these practices. Ethnology as a discourse within the context of the museum and the exhibition has been used to establish and authorise meanings in relation to Maori history and identity. The following discussions problematise these relationships within the context of emerging museum theory. These practices of representation are viewed as a 'cultural text' in order to read and understand the cultural and ideological assumptions that have informed them.
Keywords: Ethnological museums and collections; Maori; Material culture; Collection and preservation; New Zealand; Auckland; Christchurch